KARAKTERISTIK KIMIA MI KERING DENGAN SUBSTITUSI TEPUNG UBI JALAR KUNING DAN TEPUNG IKAN GABUS: Chemical Characteristics Of Dried Noodles With Substitution Of Yellow Sweet Potato Flour And Snakehead Fish Flour - Hidayah, Nur Izzatul; Berek, Thresia Dewi Kartini; Asikin, Hijrah; Sirajjudin, Sirajuddin (Media Gizi Pangan, 2024)
Dry noodles are generally made from wheat flour as the main ingredient, which is high in energy and low in other nutrients. The use of wheat flour also causes dependence on wheat imports. This study aims to determine the chemical characteristics of dried noodles substituted with yellow sweet potato flour and cork fish flour, which include moisture content, ash content, beta carotene and calcium. This type of research is a pre-experiment with a one-shot study case research design consisting of one standard formula and three treatment formulas with a concentration (%) of wheat flour: yellow sweet potato flour: cork fish flour each F0 (100:0:0), F1 (65:30:5), F2 (65:25:10), and F3 (65:20:15). Determination of moisture content was tested using the oven method, ash content using the dry sowing method, beta carotene content using the spectrophometer method, and calcium using the AAS method. The results showed that there was an increase in moisture content of 16.64%, ash content of 83.88%, beta carotene increased by 202.89% and calcium by 53.42% in dried noodles with substitutions of yellow sweet potato flour and cork fish flour compared to standard dried noodles. These results are supported by significant treatment differences in water content ρ-value = 0.008, ash content ρ-value = 0.001, beta carotene ρ-value = 0.001 and calcium ρ-value = 0.005. It is recommended for further research to pay attention to the process of making yellow sweet potato flour and processing dry noodles to maintain or minimise the decrease and damage to beta carotene levels.